Monitoring the implementation of Lean Manufacturing in a strategic area of an international company of IT - Pozo, Roselaine A. F. Teodoro (2022)
The objective of this study was to analyze the evolution of several management and monitoring practices in order to search for a better Lean Manufacturing implementation process in an IT company. The focus of the search for best implementation practices by companies, and the search for results in leaner structures, acting as global standards. In this dynamic context, the methodology adopted It was through an exploratory and qualitative research, which was carried out several surveys with 13 components of the group's strategy Company. Seeing the implementations, the biggest challenge was to show all points was positive.